The Study of Stylistics in the Novel Phosphorus, the Man Who Finds the Most Beautiful Place of Retno Mawarni’s Work - Jhanatri, Erinda (PPSDP International Journal of Education, 2024)
The aim of the research is to analyze the use of language styles in literature. The research method uses descriptive methods. The data source used is the novel Phosphor, Men Who Look for the Most Beautiful Places by Retno Mawarni, published by Sabil Yogyakarta in July 2013, with 370 pages. Based on the research results, it is known that there are eight types of imaging available; All types of imagery are used by the author in the novel Phosphorus, the man who found the most beautiful place by Retno Mawarni, namely visual imagery, auditory imagery, olfactory imagery, taste imagery, thought imagery, motion imagery, tactile imagery, and feeling imagery. Apart from imagery, a stylistic study based on rhetorical elements, namely the language style in the phosphorus novel, The Man Who Found the Most Beautiful Place by Retno Mawarni, shows that the comparative language style (figure of speech) used is the simile style (smile), the personification language style, and the allegorical language style. Contradictory language styles are hyperbole, language style, and irony. The overall style of language used by the author aims to increase the effect of the speech. The things that the author can put forward are: (1) for teaching literature in the results, additional teaching materials should be used in implementing Indonesian language and literature learning in schools; (2) for fans and lovers of literature, research results should be used as additional information as well as a reference in conducting literary research, especially regarding stylistics.